Electron-induced processes in hydroxyl cations. (21st December 2017) - Stroe, Marius Cristian; Fifirig, Magda
Abstract: Competing processes (namely, dissociative recombination, vibrational excitation and vibrational de-excitation) taking place in the collisions between slow electrons and hydroxyl cations have been investigated for electron energies below 1 eV in the framework of the multichannel quantum defect theory. Rydberg states converging to the lowest excited ionic core have been included in some computations reported here.